冬季極域でのオゾン破壊過程シュミレーションモデルの構築について - 池田,奈生; いけだ,なお; Ikeda,Nao; 林田,佐智子; 1000070180982; はやしだ,さちこ; Hayashida,Sachiko (奈良女子大学大学院人間文化研究科, 2007)
Stratospheric,ozone,destruction,by,anthropogenic,chemical,substances,is,well,known,as,one,of,the,serious,global,environmental,problems.,In,the,Polar,Regions,significant,chemical,ozone,destruction,has,been,observed.,The,understanding,of,chemically,induced,ozone,loss,in,the,polar,stratosphere,has,increased,significantly,over,the,past,decade.,However,quantitative,estimates,of,ozone,loss,remain,uncertain.,Especially,in,the,Arctic,chemical,conditions,in,the,winter,stratosphere,highly,depend,on,dynamic,processes;,thus,it,is,difficult,to,estimate,the,amount,of,chemical,ozone,destruction,quantitatively.,Therefore,a,detailed,study,on,chemical,ozone,destruction,processes,is,required.,We,constructed,a,simulation,model,of,polar,ozone,destruction,processes,using,a,chemical,box,model,combined,with,a,trajectory,tool.,The,chemical,box,model,includes,the,sufficient,number,of,chemical,reactions,in,order,to,explain,the,chemical,processes,in,winter,polar,region.,It,also,includes,the,TUV,(Thopospheric,Ultraviolet,and,Visible,Radiation,Model),to,calculate,multiple,scattering,of,solar,ultraviolet,flux,which,is,important,for,simulating,radical,species,that,are,sensitive,to,ultraviolet,intensity.,The,chemical,box,model,is,run,along,the,trajectories,to,obtain,the,mixing,ratios,of,the,chemical,species.,The,simulation,model,reproduced,ozone,destruction,processes,in,winter,polar,region,successfully.,This,report,describes,the,details,of,the,simulation,model,and,demonstrates,its,validity,for,ozone,studies. departmental bulletin paper